1979
DOI: 10.1136/bmj.1.6173.1242
|View full text |Cite
|
Sign up to set email alerts
|

Hyponatraemia and severity and outcome of myocardial infarction.

Abstract: contributing factor to the poorer results, although we do not deny that other factors may have played a part.With these reservations the three principal conclusions may be restated in relation to extradural haematoma. (a) Delay in surgical evacuation of extradural haematomas leads to increased morbidity and mortality. Specifically it appears that delays exceeding two hours are unacceptable. (b) Direct admission of patients to neurosurgical beds from the accident and emergency unit decreased the delay time. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
22
1

Year Published

1983
1983
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 8 publications
2
22
1
Order By: Relevance
“…Additionally, we tested for the interaction between pre-HD SNa levels and SNa variability in the prediction of death, by using bivariate spline analysis. Our data suggested that next to the well-known prognostic effect of hyponatremia (SNa < 136 or ≤135 mEq/L) [3][4][5][6][7]22], SNa variability has an independent adverse effect on mortality. However, of all tested variability indicators we studied, DR was the strongest predictor, robust against adjustment of the models by various relevant parameters, rendering it a suitable marker for clinical assessment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, we tested for the interaction between pre-HD SNa levels and SNa variability in the prediction of death, by using bivariate spline analysis. Our data suggested that next to the well-known prognostic effect of hyponatremia (SNa < 136 or ≤135 mEq/L) [3][4][5][6][7]22], SNa variability has an independent adverse effect on mortality. However, of all tested variability indicators we studied, DR was the strongest predictor, robust against adjustment of the models by various relevant parameters, rendering it a suitable marker for clinical assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Also, what needs to be considered is the so-called sick cell syndrome, a pathophysiological dynamic, involving the escape of intracellular osmolytes and subsequent shifts of intracellular fluid volumes to the extracellular space and subsequent dilute and lower circulating sodium, which has been described following acute events such as myocardial infarction amongst others [22,[34][35][36][37]. All these, however, remain speculative and at this point cannot be investigated with enough certainty.…”
Section: Discussionmentioning
confidence: 99%
“…Rahman et al found that 9% of patients with MI had arrhythmia. 3,1 This contradiction is probably due to routine use of beta-blocker in that study and improvement in the monitoring of our study population. 3 patients (6%) developed arrhythmia in group II and 15 patients (30%) developed arrhythmia in group-I.…”
Section: Discussionmentioning
confidence: 71%
“…They got significant ventricular fibrillation in patients with Na level 132 mmol/L and got no arrhythmia in patients with normal sodium level. 1 Previously several studies have focused on the prognostic implications of hyponatremia in patients with chronic heart failure. 4,5 In the presence of heart failure, several mechanisms promote the development of hyponatremia.…”
Section: Discussionmentioning
confidence: 99%
“…Flear and Hilton thought this hyponatremia could be caused by a redistribution of body water and solutes, due to a widespread increase in cell membrane permeability (the "sick-cell syndrome") or to a net gain of water caused by a stress-related sustained secretion of arginine vasopressin (AVP) (13). But Evans et al were unable to find the evidence for the sick-cell syndrome in hyponatremic patients with acute myocardial infarction by measurement of the osmolal gap in plasma and urine (14).…”
Section: Discussionmentioning
confidence: 99%